Effect of Accounting Ethics on Quality of Financial Reporting among Listed Commercial Banks in Rwanda Stock Exchange - Nkuranga, Wilson; Tarus, Thomas (Journal of Finance and Accounting, 2023)
Accounting ethics is an important element for enhancing the quality of financial reporting in financial institutions because it requires bank staffs to exercise integrity, objectivity and professional competence and due care. This research examined the effect of accounting ethics on quality of financial reporting among listed commercial banks in Rwanda stock exchange. The objectives of the study were to investigate the effect of accounting integrity on the quality of financial reporting among listed commercial banks in Rwanda, to determine the effect of accounting objectivity on the quality of financial reporting among listed commercial banks in Rwanda and to examine the effect of accountants’ professional competence and due care on the quality of financial reporting among listed commercial banks in Rwanda stock exchange .Theories underpinning the study are business entity theory, going concern theory and agency theories. The study used correlation design with a quantitative approach. The sample size was 363 respondents who included accounting, finance and auditing staff, heads of departments and members of the boards of directors of the four selected commercial banks. However, only 203 (56% response rate) completed the survey. Stratified simple random and purposive sampling techniques were used to select this sample. Data was analyzed through descriptive analysis. Findings for the first hypothesis (H01) show that accounting integrity has a statistically significant effect on the quality of financial reporting among selected commercial banks in Rwanda (β=.196; p<.05). This suggests that holding other factors constant, accounting integrity contributes up to 19.6% of the variation in the quality of financial reporting. For the second hypothesis (H02), it is observed that accounting objectivity has a statistically significant effect on the quality of financial reporting among selected commercial banks in Rwanda (β=.591; p<.05). Regarding the third hypothesis (H03), findings show that professional competence and due care have no statistically significant effect on the quality of financial reporting among selected commercial banks in Rwanda (β=.140; p>.05). The study recommends strengthening professional knowledge and training by investing in continuous training and development programs. Promotion of ethical practices, enhancement of staff and management collaboration and learning culture across the surveyed commercial banks are also recommended. It is hoped that the study will enable the listed commercial banks to improve ethical practices and competences among staffs so as to enhance quality of reporting. Other academicians may also find the study valuable in benchmarking their studies on the same subject. Keywords: Accounting Ethics, Quality of Financial Reporting, Commercial Banks, Rwanda Stock Exchange